Diversity and Functional Role of The Coleoptera Order in The Nglanggeran Ancient Volcano Area, Yogyakarta - Salsabila, Aulia Rosada; Rahmawati, Yunita Fera; Jamallika, Sa’adah Nurwidyani; Rahmawati, Dwi; Putri, Zahwa Actamevia; Rahayu, Sofia Ery (Biosfer: Jurnal Tadris Biologi, 2023)
The aim of this research that was conducted in the Nglanggeran Ancient Volcano Area Yogyakarta was to determine the diversity and functional role of Coleoptera in the area. The research was conducted by survey, with observation method, in March-April 2021. Data were collected through purposive random sampling with Sorting, Yellow Pan Trap, and Hunting methods. The results of research at six stations indicated the presence of 30 individuals belonging to four families of Arthropoda order Coleoptera, namely Lilioceris lilii (Chrysomelida), Charidotella sexpunctata (Chrysomelidae), Lytta stygica (Meloidae), Anisodactylus nigerrimus (Carabaeidae), and Harmonia axyridis (Coccinellidae). Based on their functional roles, the Carabaeidae and Coccinellidae families that dominate this finding act as predators, while the Chrysomelidae and Meloidae families act as herbivores. The results of the analysis using PAST 4.07b software show that Coleoptera diversity in the area is included in the low diversity index category with a value of 0.773, a low species richness index with a value of 0.6213, and an evenly distributed abundance index with a value close to 1.ABSTRAK: Penelitian yang dilakukan di Kawasan Gunung Api Purba Nglanggeran Yogyakarta ini bertujuan untuk mengetahui keanekaragaman dan peran fungsional Coleoptera di kawasan tersebut. Penelitian dilakukan secara survei, dengan metode observasi pada bulan Maret-April 2021. Data dikumpulkan melalui purposive random sampling dengan kombinasi metode Sorting, Yellow Pan Trap, dan Hunting. Hasil penelitian di enam stasiun  menunjukkan adanya 30 individu yang termasuk ke dalam empat famili Arthropoda ordo Coleoptera yaitu Lilioceris lilii (Chrysomelida), Charidotella sexpunctata (Chrysomelidae), Lytta stygica (Meloidae), Anisodactylus nigerrimus (Carabaeidae), dan Harmonia axyridis (Coccinellidae). Berdasar peran fungsionalnya, famili Carabaeidae dan Coccinellidae yang mendominasi temuan ini berperan sebagai predator, sedangkan famili Chrysomelidae dan Meloidae berperan sebagai herbivor. Hasil analisis menggunakan software PAST 4.07b menunjukkan bahwa keanekaragaman Coleoptera di kawasan tersebut termasuk ke dalam kategori indeks keanekaragaman rendah dengan nilai 0,773, indeks kekayaan jenis rendah dengan nilai 0,6213, dan indeks kelimpahan yang merata dengan nilai mendekati 1.